Towards enterprise-wide pharma 4.0 adoption - Vincent Junior Phiri; Ilham Battas; Atae Semmar; Hicham Medromi; Fouad Moutaouakkil (Scientific African)
The adoption of Industry 4.0 in the pharmaceutical industry is referred to as Pharma 4.0. Pharma 4.0 procures pharmaceutical organizations many significant benefits ranging from operational efficiency to regulatory compliance. This study evaluates existing Pharma 4.0 adoption frameworks in literature and aims to develop a structured and adaptable Pharma 4.0 enterprise-wide adoption conceptual framework. A systematic review was conducted to identify and analyze existing Pharma 4.0 frameworks. The examined frameworks were categorized into Manufacturing and Quality Management, Supply Chain Management, Clinical Trials and R&D Digitalization, Workforce Competence, and Pharma 5.0. Analysis of the identified frameworks reveals that while they offer strategies for digital transformation, they focus solely on specific areas. In response, a conceptual Pharma 4.0 framework is proposed, emphasizing organizational readiness assessment, core technology integration, cybersecurity and data management, system integration, and continuous improvement. This framework provides a practical roadmap for Pharma 4.0 adoption, improving regulatory compliance and operational efficiency. Also, the framework supports a diverse range of pharmaceutical organizations, including small and medium-sized enterprises (SMEs) in Africa and other developing nations. Thus, this study contributes a novel structured framework for enterprise-wide Pharma 4.0 adoption and addresses its key implementation barriers by establishing critical success factors.